STEAP1 Regulates Tumorigenesis and Chemoresistance During Peritoneal Metastasis of Gastric Cancer - Yuan-Yu Wu (Frontiers in Physiology, 2018)
In China, majority of the mortality in gastric cancer are associated with peritoneal metastasis. Since most gastric tumors are metastatic at initial diagnosis, the treatment of gastric cancer is limited to radical resection. Therefore, it is imperative to identify diagnostic and prognostic biomarkers. From 2014 to 2015, 20 patients were enrolled in the study. To search translationally upregulated genes in the context of epithelial to mesenchymal transition (EMT), polysome profiling was performed. The MTT, migration, and invasion assay were conducted to determine cell proliferation, migration, and invasion ability respectively. Experiments of gain and loss of function were performed using the overexpression plasmid, siRNA, and shRNA. Xenograft assay was established using nude mice to explore the role of targets translationally upregulated gene in vivo. Polysome profiling defined the landscape of translationally regulated gene products with differential expression between non-metastatic and metastatic cohorts. Six-transmembrane epithelial antigen of the prostate 1 (STEAP1) was found to be the most translationally upregulated gene product in either experimental groups. STEAP1 was found to be required for cell proliferation, in vitro migration and invasion, and in vivo tumorigenesis. RNAi-mediated silencing of STEAP1 potentiated chemosensitivity of the MKN45 cells to docetaxel treatment, highlighting the importance of STEAP1 as a novel biomarker in gastric cancer patients with peritoneal metastasis. STEAP1 is thus induced translationally and its expression promotes proliferation, migration, invasiveness, and tumorigenicity of gastric cancer. STEAP1 can be a potent candidate for designing of targeted therapy.